STUDY OF MODIS-AQUA DATA FOR MAPPING TOTAL SUSPENDED MATTER (TSM) IN COASTAL WATERS - Bambang Trisakti; Parwati; Syarif Budhiman (BRIN, 2005)
The MODIS-Aqua data have been studied to map TSM distribution in coastal waters. TSM algorithm model for MODIS data with spatial resolution of 250 m, 500 m and 1000 m was developed by correlating the TSM derived from spectral values of MODIS and the TSM derived from Landsat-7 ETM data using the calibrated algorithm. Statistical test was conducted to see normality of data and level of influence from both parameters. Analysis was conducted to see the change of spectral value from bands of MODIS data with resolution of 1000 m towards the change of level of TSM concentration. The results showsthat the TSM algorithm model is in the form of power (Xa) with the highest correlation coefficient is obtained from the correlation between the Landsat TSM value with the quantification of band 1 and band 2 of MODIS data for spatial resolution 250 m, ratio of band 4 and band 3 for spatial resolution 500 m, and ratio of band 13 and 11 for spatial resolution 1000 m. The pattern of TSM distribution in coastal waters can be identified in more accurate using MODIS data with resolution of 250 m and 500 m. The analysis result of the curve of MODIS spectral value data with resolution 1000 m shows that the change of TSM concentration influences significantly to the form of curve of spectral value, especially for band 11 - 16 ( visible green, red and NIR).